2015
DOI: 10.5565/rev/qpsicologia.1283
|View full text |Cite
|
Sign up to set email alerts
|

Mapped vulnerabilities, Located violences: Experiences of transvestites and transgender individuals in Brazil

Abstract: ResumoO presente artigo discute as formas de violência, seus modos de atuação, naturalização e invisibilidade, às quais as pessoas travestis e transexuais são submetidas em Santa Catarina, Brasil. A partir da aplicação de questionários a 100 pessoas trans, foi possível elaborar um perfil psicossocial desta população e identificar as violências específicas pelas quais passa, além de seus principais agentes. Os tipos mais frequentes são a discriminação, as violências psicológica, física e institucional, sendo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
2
0
5
Order By: Relevance
“…Essa violência se revela de forma verbal, por meio de negligências, tratamentos desumanizados, ameaças, punições, repreensões, abuso de poder, não alívio da dor e abuso sexual 11 . Estudo mapeou que 37% da população trans estudada sofreu homofobia; 36% tiveram ausência de atendimento; 27%, recusa e abuso de poder; 24%, demora excessiva no atendimento; e 40% sofreram algum tipo de violência física ou psicológica dentro do serviço de saúde 30 . Toda essa plêiade de situações incide em demandas de Saúde Mental para o público trans.…”
Section: Discussionunclassified
“…Essa violência se revela de forma verbal, por meio de negligências, tratamentos desumanizados, ameaças, punições, repreensões, abuso de poder, não alívio da dor e abuso sexual 11 . Estudo mapeou que 37% da população trans estudada sofreu homofobia; 36% tiveram ausência de atendimento; 27%, recusa e abuso de poder; 24%, demora excessiva no atendimento; e 40% sofreram algum tipo de violência física ou psicológica dentro do serviço de saúde 30 . Toda essa plêiade de situações incide em demandas de Saúde Mental para o público trans.…”
Section: Discussionunclassified
“…To some extent, the people belonging to these groups are perceived as being responsible for their acts, and this result mainly indicates that the Brazilian normative context does not exert any strong pressure to condemn discrimination towards groups who have sexual behaviours that are perceived as different from the traditional heteronormative pattern (Alencar, Neves & Parente, 2016;Freires, 2015). The most disturbing feature is that, as they are not protected by the antiprejudice norm, these are the groups that are the greatest victims of aggression and violence in Brazil (Bonassi et al, 2015), as pointed out in the study by Silva et al (2016). In a sample of transvestites and transsexuals, the authors analysed the types of violence to which they were subjected and revealed that 91% had already been victims of verbal violence, 58% psychological violence and 33% physical violence.…”
Section: Discussionmentioning
confidence: 99%
“…24 The mapping of the presented vulnerabilities shows the forms of violence suffered by the transsexual population and emphasizes that the barriers to health services need to be broken beyond access but also under the integral perspective of health care. 25 The rigid sexual morality marked by male sexual domination and gender oppressive relationships present vulnerability marked by prejudice, discrimination, lack of equality and equal rights which lead to a set of conditions that exposes the transsexual population to the non-use of condoms as well as inadequate treatment.…”
Section: Discussionmentioning
confidence: 99%